The Effects of Margarine Substitution with Peanut Paste on The Characteristics of Sago Cookies - Makahity, Henzye; Tuhumury, Helen Cynthia Dewi; Palijama, Syane (Journal of Applied Agricultural Science and Technology, 2024)
The principle of making sago cookies without wheat flour through the substitution of margarine with peanut paste is predicted to boost the nutritional content of cookies and also employ alternative components to replace margarine to develop products that are acceptable to consumers. This study aimed to determine the right concentration of peanut paste to substitute for margarine in the manufacture of sago cookies. This study was designed using a one-factor Complete Randomized Design (CRD), namely the substitution of margarine with peanut paste at five substitution levels of 100:0%, 75%:25%, 50%:50%, 25:75%, and 0%:100% repated twice. Observed variables include moisture content, ash content, protein content, fat content, carbohydrate content, cookie thickness, cookie diameter, cookie spreading ratio, and sensory characteristics. The results showed that the optimal treatment to produce sago cookies, characterized by the highest acceptance across all sensory attributes such as color, taste, aroma, texture, and overall likeness, involves the substitution of margarine with peanut paste at a ratio of 75% to 25%. Cookies subjected to this treatment exhibited specific characteristics, including a moisture content of 3.72%, an ash content of 1.75%, a protein content of 10.05%, a fat content of 17.56%, and a carbohydrate content of 66.93%. Additionally, these cookies possessed a thickness of 0.54 cm, a diameter of 5.30 cm, and a spreading ratio of 10.15. Furthermore, these cookies were characterized by a slightly broken surface, a slightly irregular shape without damage, a texture that crumbles slightly when pressed with fingers, a crispiness when bitten, and easy crumbling in the mouth. They also feature a slight sago flavor and a distinct sago taste. Overall, the 75% margarine to 25% peanut paste substitution ratio yields cookies that encompass a comprehensive profile of desirable sensory qualities.